Delayed Respiratory Insufficiency and Extramuscular Abnormalities in Selenoprotein N-Related Myopathies - Zhang, Shu; Lei, Lin; Fan, Zhirong; Su, Shengyao; Duo, Jianying; Luan, Qinrong; Lu, Yan; Di, Li; Wang, Min; Da, Yuwei (Frontiers in Neurology, 2021)
Background: Selenoprotein N-related myopathies (SEPN1-RM) are a subset of congenital myopathies caused by mutations of Selenoprotein N gene (SELENON or SEPN1). Clinical phenotype is considered highly consistent and little attention has been given to extramuscular abnormalities. Methods: We reported clinical, histopathological and genetic features of 4 Chinese SEPN1-RM patients and performed literature review on delayed respiratory insufficiency and extramuscular involvement. Results: Four patients exhibited both typical and atypical clinical features of SEPN1-RM. The classical manifestations included axial and limb girdle weakness, spinal rigidity, scoliosis, respiratory insufficiency and multiminicore morphological lesions. However, high inter-individual variability was noticed on disease severity, especially the onset of respiratory involvement. Two adult patients postponed respiratory insufficiency to the third decade of life, while two juvenile patients manifested early hypo-ventilation with puberty exacerbation. As atypical features, extramuscular involvement of weight gain, subcutaneous adipose accumulation, intellectual disability and mild cardiac changes were observed. Molecular findings revealed 3 novel mutations of SELENON, c.1286_1288 del CCT, c.1078_1086dupGGCTACATA and c.785 G>C. 10 cases with delayed respiratory insufficiency were identified from previous publications. 18 studies described extramuscular abnormalities, including joint contractures, alterations of BMI, mild cardiac changes and insulin resistance. Intellectual impairment was extremely rare. Conclusion: SEPN1-RM should be considered as a differential diagnosis in adult patients with delayed respiratory involvement. Extramuscular involvement like body composition alterations deserves more clinical attention. The novel mutations of SELENON widened the genetic spectrum of SEPN1-RM patients.